PENGARUH PENGGUNAAN BAHAN AJAR FISIKA BERORIENTASI METODE PEMECAHAN MASALAH DALAM IMPLEMENTASI STANDAR PROSES TERHADAP HASIL BELAJAR SISWA KELAS XI SMAN 7 PADANG - Azianul Aslam (Universitas Negeri Padang, 2013)
Learning in process standard asks learning material. In fact, the use of learning materials is notoptimal yet. A solution to solve this problem is using learning material oriented problem solving method.This research aims to investigate the effect of using teaching material oriented problem solving method inimplementation of process standard toward students’ learning outcomes in SMAN 7 Padang. Type of thisresearch is Quasi Experimental Research which is designed by using Randomized Control Group OnlyDesign. The population in this research consisted of 4 classes from XI IPA 3 to XI IPA 6 in SMAN 7Padang. The technique used to take the sample is purposive sampling. The sample of the research is gradeXI IPA 5 as experimental class and XI IPA 6 as control class. The technique of data collection are writtentest for cognitive aspect and observation sheet for affective and psychomotor aspect. The technique of dataanalysis is done in hypothesis test through t-Test in real level 0,05 for cognitive, affective, and psychomotoraspect. The results obtained from this research as follows: first, the students’ score for each aspects is 76,182in cognitive, 81, 333 in affective, and 78, 182 in psychomotor. The result of students score is above KKMthat is standardized by the school 75. Second, physics learning material oriented problem solving method isnot very influential to increase students’ score in cognitive aspect but it has been influence in affective andpsychomotor aspect.Keywords: Learning Material, Problem Solving Method, Process Standard, Learning Outcomes